2012
DOI: 10.1021/jo202359e
|View full text |Cite
|
Sign up to set email alerts
|

A Multimetallic Piano-Stool Ir–Sn3 Catalyst for Nucleophilic Substitution Reaction of γ-Hydroxy Lactams through N-Acyliminium Ions

Abstract: A multimetallic piano-stool complex [Cp*Ir(SnCl(3))(2){SnCl(2)(H(2)O)(2)}] (1) having Ir-Sn(3) motif has been synthesized from [Cp*IrCl(2)](2) and SnCl(2). The multimetallic complex catalytically promotes the nucleophilic substitution reaction (here after α-amidoalkylation reaction) of γ-hydroxylactams generated from phthalimidals to obtain decorated isoindolinones in excellent yields. Succinamidals, however, lead to the substituted pyrrolidinones (thermodynamic control product) via S(N)1-type path as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Phthalic anhydride‐derived γ‐hydroxylactams containing the aromatic nucleophiles reacted in the presence of only 1 mol% of 1 under mild reaction conditions to provide the cyclized products 4a and 4b in excellent yields. Compared to the intermolecular version where less electron‐rich arenes like toluene remained unreactive,20a here the reaction took a much longer time (12 h) to afford 95% of cyclized product 4b . Electron‐poor arenes remained unreactive towards the cyclization reaction.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Phthalic anhydride‐derived γ‐hydroxylactams containing the aromatic nucleophiles reacted in the presence of only 1 mol% of 1 under mild reaction conditions to provide the cyclized products 4a and 4b in excellent yields. Compared to the intermolecular version where less electron‐rich arenes like toluene remained unreactive,20a here the reaction took a much longer time (12 h) to afford 95% of cyclized product 4b . Electron‐poor arenes remained unreactive towards the cyclization reaction.…”
Section: Resultsmentioning
confidence: 82%
“…In our previous report on 1 ‐catalyzed intermolecular α‐amidoalkylation reactions with a variety of carbon nucleophiles we found that, along with electron rich‐arenes and heteroarenes, 4‐hydroxycoumarin could also be employed for the successful formation of isoindolinone derivatives in excellent yields 20a. So here we thought to extend the scope of the alkylation reaction with other β‐dicarbonyl compounds.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations